The Mediation Role of Resource Accessibility between Perceived Social Support and e-Entrepreneurial Intention of Female Students in Saudi Arabia - Alzamel, Samar; Mohammed Nazri Mohd Nor; Safiah Binti Omar; Mohammed Mustafa Mohammed (Journal of Technology Management and Business, 2020)
Entrepreneurship has become highly popular among younger people due to the booming of cyber platforms, specifically in online businesses. However, the motivation behind students’ aspirations to start online businesses is yet to be rarely examined within the extant literature. Consequently, the current study seeks to explore the mediating role of resource accessibility on the relationship between perceived social support and e-entrepreneurial intention among female students in Saudi Arabia. The study involved distribution of 376 online questionnaires among undergraduate female students studying business related subjects in public and private universities in Saudi Arabia. The study findings suggest that perceived social support has a positive influence on e-entrepreneurial intention and resource accessibility among the students. Moreover, there is an indication from the findings that resource accessibility plays a significant mediating role between perceived social support and e-entrepreneurial intention. The study findings contribute to the extant literature of e-entrepreneurship, demonstrating the significance of supporting students to start their own online businesses by providing them full access to the available resources. Keywords: Management, e-Entrepreneurship, Social Support, Resource Accessibility, Female Intention